Establishment of the Authority for Anti-Money Laundering. Why Does the European Union Need to Institutionalize Anti-Money Laundering? - Tomasz Matras (Review of European and Comparative Law)
The Regulation of the European Parliament and of the Council of 31 May 2024 establishing the Authority for Anti-Money Laundering and Countering the Financing of Terrorism (AMLA) is an important step in combating money laundering and the financing of terrorism. This article outlines why this initiative was deemed necessary and what the objectives and powers of the new Authority will be. The primary method used during the research was the formal-dogmatic method through an analysis of the provisions regulating AML. The new Authority’s goals and functions were verified using legal acts, reports and studies from European Union bodies. On the basis of these, conclusions are presented on the purposefulness of the AMLA’s establishment, its scope of tasks and how it is expected to function. Some of the proposed assumptions – especially regarding the effectiveness of the direct supervision the AMLA is to perform – were subject to critical analysis. The research results show that, to increase the effectiveness of overall AML policy in the European Union, the new Authority must cooperate successfully with both EU and national authorities – primarily the Financial Intelligence Units of Member States.